Cellular Interactions and Inflammation in the Pathogenesis of Cutaneous T-Cell Lymphoma - Stolearenco, Veronica; Namini, Martin R. J.; Hasselager, Siri S.; Gluud, Maria; Buus, Terkild B.; Willerslev-Olsen, Andreas; Ødum, Niels; Krejsgaard, Thorbjørn (Frontiers in Cell and Developmental Biology, 2020)
Cutaneous T-cell lymphoma (CTCL) comprises a group of lymphoproliferative diseases characterized by the accumulation of malignant T cells in chronically inflamed skin lesions. In early stages, the disease presents as skin patches or plaques covering a limited area of the skin and normally follows an indolent course. However, in a subset of patients the cutaneous lesions develop into tumors and the malignant T cells may spread to the lymphatic system, blood and internal organs with fatal consequences. Despite intensive research, the mechanisms driving disease progression remain incompletely understood. While most studies have focused on cancer cell-intrinsic oncogenesis, such as genetic and epigenetic events driving malignant transformation and disease progression, an increasing body of evidence shows that the interplay between malignant T cells and non-malignant cells plays a crucial role. Here, we outline some of the emerging mechanisms by which tumor, stromal and epidermal interactions may contribute to the progression of CTCL with particular emphasis on the crosstalk between fibroblasts, keratinocytes and malignant T cells.